2018
DOI: 10.1016/j.jhydrol.2018.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of groundwater recharge via percolation outputs from a rainfall/runoff model for the Verlorenvlei estuarine system, west coast, South Africa

Abstract: 11Wetlands are conservation priorities worldwide, due to their high biodiversity and productivity, but are 12 under threat from agricultural and climate change stresses. To improve the water management practices 13 and resource allocation in these complex systems, a modelling approach has been developed to estimate 14 potential recharge for data poor catchments using rainfall data and basic assumptions regarding soil and 15 aquifer properties. The Verlorenvlei estuarine lake (RAMSAR #525) on the west coast of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 27 publications
(26 reference statements)
4
27
1
Order By: Relevance
“…To our knowledge, the GloWPa-TGR-Crypto model cannot be validated through the direct comparison of measured surface water values because this method ignores certain factors, such as the infiltration pathways and transport via soils and shallow groundwater to surface water ( Bogena et al, 2005 ; Vermeulen et al, 2017 ; Watson et al, 2018 ), the overflow of sewage treatment plants during the flood period ( Xiao et al, 2017 ), traditional dispersive small-scale peasant production ( Li et al, 2016 ), and the excretion of wildlife ( Atwill, Phillips & Rulofson, 2003 ). The pathogen loading data of these factors are not readily available.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the GloWPa-TGR-Crypto model cannot be validated through the direct comparison of measured surface water values because this method ignores certain factors, such as the infiltration pathways and transport via soils and shallow groundwater to surface water ( Bogena et al, 2005 ; Vermeulen et al, 2017 ; Watson et al, 2018 ), the overflow of sewage treatment plants during the flood period ( Xiao et al, 2017 ), traditional dispersive small-scale peasant production ( Li et al, 2016 ), and the excretion of wildlife ( Atwill, Phillips & Rulofson, 2003 ). The pathogen loading data of these factors are not readily available.…”
Section: Discussionmentioning
confidence: 99%
“…Daily totals of precipitation and solar radiation, mean daily relative humidity, temperature, windspeed and maximum and minimum daily temperature were collected for the period 1988-2002 (including a 2-year initialization period). The data were attained from the World Meteorological Organisation (WMO) as global surface summary of the day (GSOD) data [23], as well as the Agricultural Research Council (ARC), the South African Weather Services (SAWS), the Department of Water Affairs and Sanitation, South Africa (DWS), the South African Earth Observation Network [45] and previous JAMS/J2000 model data [18,[46][47][48][49][50]. In total, 97 precipitation, 24 temperature, 12 relative humidity, 15 windspeed and seven solar radiation stations were used (Table 2).…”
Section: Climate Inputsmentioning
confidence: 99%
“…The model calibration was performed using a semi-automated procedure (e.g., [66]), which utilized the non-dominated sorting genetic algorithm (NSGA-II) [67] to explore the 'optimal' parameter space and model expertise from other applications [18,46,48,49,68,69] to finally select quantifiable model parameters for the region. For the calibration and validation of the Velorenvlei, Berg, Bot and Breede catchments, the time series was split into two (e.g., [70]), with (1) calibration from 01-01-1990 to 31-12-1995 and (2) validation from 01-01-1996 to 01-01-2002.…”
Section: Model Calibration and Validationmentioning
confidence: 99%
“…In this study, parameters that 323 were used to control the ratio of interflow to percolation were adjusted, which in the J2000 324 model include a slope (SoilLatVertDist) and max percolation value. The sensitivity analysis 325 conducted by Watson et al, (2018) showed that for high flow conditions (E2) (Nash-Sutcliffe 326 efficiency in its standard squared), model outputs are most sensitive to the slope factor, while 327 for low flow conditions (E1) (modified Nash-Sutcliffe efficiency in a linear form) the model 328 outputs were most sensitive to the maximum infiltration rate of the soil (ie. the parameter 329 maxInfiltrationWet) (Supplementary: Figure 1).…”
Section: Model Sensitivity 321mentioning
confidence: 99%
“…Agriculture is the 148 dominant water user in the sub-catchment with an estimated usage of 20 % of the total recharge 149 (DWAF, 2003;Watson et al, submitted), with the main food crop being potatoes. For further 150 information regarding the study site refer to Watson et al, (2018). 151…”
mentioning
confidence: 99%